(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Philosophy recognizes the vital principles of morality and religion, striving to understand the complex nature of their relationship. Ultimately, it prevents the descent into moralism and fanaticism, ensuring the preservation of true human principles in both religion and morality. Ethics elevates the significance of philosophy, establishing its necessity for both religious experience, which requires its guiding role, and the moral life of a person.